Skewness and the relation between risk and return - Theodossiou, Panayiotis; Savva, Christos S. (My University, 2016)
The relationship between risk and return has been one of the most important and extensively investigated issues in the financial economics literature. The theoretical results predict a positive relation between the two. Nevertheless, the empirical findings so far have been contradictory. Evidence presented in this paper shows that these contradictions are the result of negative skewness in the distribution of portfolio excess return and the fact that the estimation of intertemporal asset pricing models are based on symmetric log-likelihood specifications.
Keywords: GARCH-M; Risk-return trade-off; SGT distribution